Colour‐based foraging diverges after multiple generations under different light environments. (19th February 2019) - Cole, Gemma L.; Lynn, Jessica C. B.; Kranz, Alexandrea M.; Endler, John A.
Abstract: When the environment changes, sensory systems can adapt plastically or evolve genetically to the new surroundings, and traits and behaviours reliant on these sensory systems may also change, leading to altered evolutionary trajectories. We tested for differences in colour‐based foraging preferences of guppies ( Poecilia reticulata ) that lived for 6–10 generations under each of three light environments (green, lilac or control) to determine whether evolution under different light environments alters visually based behaviour. When tested in a common light environment, we found differences in pecking behaviour between treatments that were likely due to changes in the visual system. Pecking behaviour towards green stimuli was consistent across light treatments, possibly reflecting the importance of detecting green algae in the wild. The blue stimulus was only pecked at by fish from the control environments. Behaviour towards long wavelength stimuli varied, possibly due to the polymorphic nature of the long wavelength opsins. These results are consistent with one component of sensory drive but do not allow us to conclude whether these differences are due to plastic or evolved responses.